Role of Consumption Emotions Mediate Perceived Service Fairness to the Service Satisfaction and Its Impact on Customers’ Behavioral Intentions - Ebrahimi, Abolghasem; Abbasi, Abbas; Khalifeh, Mojtaba; Samizadeh, Mehdi; Abkhiz, Farzaneh (UI Scholars Hub, 2021)
Considering that customers’ emotions toward received services are evaluated in light of fairness and equity theory, the purpose of this study is to investigate the effect of customers’ perceptions and emotions of received services on their behavioral intentions. Data were collected from 329 questioners that were distributed among Mellat bank customers, and hypotheses and the conceptual model were analyzed based on the data collected through structural equation modeling in AMOS 18. Results showed that three dimensions of interactional, procedural, and distributive justice affected customers’ emotions (negative and positive) and satisfaction. Customers’ emotions were also found to be having a mediating role in the relationship between perceptions of fairness (except procedural fairness) and customer satisfaction. The other results are the effect of customer satisfaction on behavioral intentions (repeat purchases and Word-of-mouth advertising). Finally, the study suggests some practical solutions and future research topics.